Stratifikasi Sosial dan Perjuangan Kelas dalam Perspektif Sosiologi Pendidikan - Maunah, Binti (Taallum: Jurnal Pendidikan Islam, 2015)
It is a fact that social stratum is an effect of the differences of education, economy, or ancestry. It appears since the human beings lived together in a social organization. The main cause for the appearance of social strata is the imbalance between rights and obligation of the member of society and the unfair share of power in the society. Social stratum and education is mutually influential in two ways. First, high education needs fund and motivation. Second, type of education determines the social stratum. In other words, education does not only provide skills but also cause some differences in term of way of life and mental life.